Combined effect of fasting blood glucose and serum uric acid on nonalcoholic fatty liver disease - Yifan Hao; Xuerui Li; Yiting Zhang; Jun Zheng; Yuyang Miao; Jin Tan; Qiang Zhang (Lipids in Health and Disease)
Abstract Background This study sought to investigate the independent and synergistic impacts of fasting blood glucose (FBG) and serum uric acid (SUA) levels on non-alcoholic fatty liver disease (NAFLD) in participants with and without type 2 diabetes mellitus (T2DM). Method A total of 12,430 participants (mean age: 54.34 ± 15.23, 34.34% female) were enrolled through the Health Screening Center of Tianjin Medical University General Hospital. FBG was classified as < 6 mmol/L, 6–7 mmol/L, and ≥ 7 mmol/L. SUA was classified into two categories: normal SUA and hyperuricemia (SUA level ≥ 420 µmol/L for men, ≥ 360 µmol/L for women). T2DM was ascertained through self-reported data. The diagnosis of NAFLD is established via abdominal ultrasound imaging. Logistic regression models and interaction effect models are used for data analysis. Result Of the 12,430 participants, 4846 (38.99%) were diagnosed with NAFLD. In comparison to individuals with FBG < 6 mmol/L and no self-reported T2DM, those with FBG ≥ 7 mmol/L and no self-reported T2DM exhibited the highest prevalence of NAFLD (odds ratio [OR] 2.91, 95% CI 2.16–3.93) following multi-adjusted analysis. In the joint effect analysis of FBG and SUA, FBG ≥ 7 mmol/L and hyperuricemia were linked to a greater prevalence of NAFLD compared to FBG < 6 mmol/L and normal SUA, both in individuals with self-reported T2DM (OR 2.92, 95% CI 1.68–5.05) and those without self-reported T2DM (OR 7.87, 95% CI 3.57–17.34). An additive interaction existed between FBG and SUA regarding NAFLD in individuals without self-reported T2DM (AP 0.488, 95% CI: 0.068–0.909, P = 0.02). Conclusion Elevated FBG levels are associated with NAFLD irrespective of self-reported T2DM status. The concomitant elevation of FBG and SUA levels exhibits a significant correlation with NAFLD, particularly in individuals lacking self-reported T2DM.